From sustainable development to green growth: The abandonment of the social character of development - Vavouras, Ioannis (Social Cohesion and Development, 2016)
Sustainable development, the basic social, economic and ecological strategy of the late 20th century at the national and international level, is gradually giving its place to green growth. This change is associated with important socioeconomic adjustments. We argue that although green growth has moved away from the one-dimensional concept of economic growth, by incorporating the environmental dimension, apart from the economic one, at the same time it neglects the social aspect that constitutes the third dimension of sustainable development. Therefore, the widely proposed in recent years green growth strategy could be characterized as a major social drawback.